The impact of level of education on age-related deficits in associative memory: Behavioral and neuropsychological perspectives. (June 2017) - Peterson, Dwight J.; Gargya, Sanchita; Kopeikin, Ksenia S.; Naveh-Benjamin, Moshe
Abstract: Older adults have difficulty forming associations and binding distinct item components despite mostly preserved item memory potentially because they rely on more automatic, rather than strategic, processing when attempting to form, store, and retrieve associations from memory. An intriguing possibility is that older adults with greater access to strategic processes (e.g., those with a high level of education) may be less susceptible to age-related associative memory deficits. Two experiments assessed the degree to which a high level of education provides an effective dose of cognitive reserve (CR), potentially preserving associative memory. Standard younger and older adults' item and associative memory performance was compared to older adults who had attained a high level of education (mostly doctoral degrees). In both experiments (Experiment 1: person–action pairs; Experiment 2: unrelated word pairs), consistent evidence was found that older adults, regardless of the level of education, exhibited an age-related associative memory deficit relative to younger adults. Interestingly, neuropsychological assessment of both older adult groups revealed greater frontal lobe, but not enhanced medial temporal lobe, functioning in the highly educated. As such, although the highly educated older adults exhibited greater frontal lobe functioning than the standard older adults, this did not aid in the reduction of the age-related associative memory deficit.